School Engagement pada Siswa SMA Pangudi Luhur Van Lith Muntilan - Polii, Evi Ema Victoria (Zenit, 2015)
This research aims to find the description and the profiles of School Engagement that being applied by the students of Pangudi Luhur Van Lith high school. School Engagement is included in three types of multifaceted components which are behavioral, emotional and cognitive. The data wascollected by using School Engagementâs Questionare that was contructed from theoretical concept of School Engagement from Fredericks, Blumenfeld and Paris (2005). The data has been analyzed by using descriptive analysis method to find the conclusion. The result shows that 33,87% of the studentshave engaging in schoolâs activity. In contrary, 66,13% of the students still not engaging yet and divided into 5 different profiles.Keywords : School Engagement, Behavioral, Emotional, Cognitive